Construct validation of the hybrid model of posttraumatic stress disorder: Distinctiveness of the new symptom clusters. (March 2018) - Silverstein, Madison W.; Dieujuste, Nathalie; Kramer, Lindsay B.; Lee, Daniel J.; Weathers, Frank W.
Highlights: Significant heterogeneity emerged for dysphoric arousal, anxious arousal, and externalizing behavior. There was less evidence for the distinctiveness of negative affect and anhedonia. This model might not provide a meaningful framework for understanding which PTSD symptoms relate to associated features. Abstract: Despite the factor analytic support for the seven-factor hybrid model (Armour et al., 2015) of posttraumatic stress disorder (PTSD), little research has examined the degree to which newly established symptom clusters (i.e., negative affect, anhedonia, dysphoric arousal, anxious arousal, externalizing behavior) functionally and meaningfully differ in their associations with other clinical phenomena. The aim of the current study was to examine the degree to which newly established PTSD symptom clusters differentially relate to co-occurring psychopathology and related clinical phenomena through Wald testing using latent variable modeling. Participants were 535 trauma-exposed undergraduates who completed the Posttraumatic Stress Disorder Checklist for DSM-5 (PCL-5;Weathers et al., 2013 ) and Personality Assessment Inventory (PAI; Morey, 1991). As expected and in line with results from previous studies, significant heterogeneity emerged for dysphoric arousal, anxious arousal, and externalizing behavior. However, there was less evidence for the distinctiveness of negative affect and anhedonia. Results indicate that only some of the newly established symptom clusters significantly differ in their associations with related clinical phenomena and that the hybrid model might not provide a meaningful framework for understanding which PTSD symptoms relate to associated features. Limitations include a non-clinical sample and reliance on retrospective self-report assessment measures.